2020
DOI: 10.3390/app10186450
|View full text |Cite
|
Sign up to set email alerts
|

The Oral Microbiome of Healthy Japanese People at the Age of 90

Abstract: For a healthy oral cavity, maintaining a healthy microbiome is essential. However, data on healthy microbiomes are not sufficient. To determine the nature of the core microbiome, the oral-microbiome structure was analyzed using pyrosequencing data. Saliva samples were obtained from healthy 90-year-old participants who attended the 20-year follow-up Niigata cohort study. A total of 85 people participated in the health checkups. The study population consisted of 40 male and 45 female participants. Stimulated sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
0
2
1
Order By: Relevance
“…In the study of healthy children, Proteobacteria was abundant in the group without dental caries, and Firmicutes and Bacteroides were abundant in the group with dental caries [21]. A study of healthy elderly people found that Firmicutes and Veillonella were abundant at the phyla level [22,23]. This was markedly different from the BS group in this study, in which Neisseria, Porphyromonas and Streptococcus were significant.…”
Section: Discussioncontrasting
confidence: 62%
“…In the study of healthy children, Proteobacteria was abundant in the group without dental caries, and Firmicutes and Bacteroides were abundant in the group with dental caries [21]. A study of healthy elderly people found that Firmicutes and Veillonella were abundant at the phyla level [22,23]. This was markedly different from the BS group in this study, in which Neisseria, Porphyromonas and Streptococcus were significant.…”
Section: Discussioncontrasting
confidence: 62%
“…Microbiome analysis was conducted by Bioconductor on free software R ver 4.03. The package used in this study were microbiome, phyloseq, vegan, ape, knitr and Rtsne [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…However, some pathogenic species are predominant in healthy subjects. For example, predominant bacteria such as the S. sinensis group and S. pneumoniae group are known to be the pathogens for pneumonia [6,7].…”
mentioning
confidence: 99%